A comparative study of linear measurements on facial skeleton with frontal and lateral cephalogram - Chandra Sekhar Gandikota; Naveen Rayapudi; Padma Latha Challa; Shubhaker Rao Juvvadi; P V Yudhister; Gutti Hariprasad Rao (Wolters Kluwer Medknow Publications, 2012)
Objective: To compare the accuracy of linear measurements on lateral and frontal cephalograms with gold standard skull measurements . Materials and Methods: Based on the specific criteria including reliable occlusion and condyles fitting in glenoid fossa, 15 dry human skulls were selected from a larger collection. Lateral and frontal cephalograms were taken of each skull by standardized methods. Steel ball bearings were used to identify the anatomic landmarks. Linear measurements in midsagittal plane were made on all three records. Intraclass correlation coefficients, Pearson's correlation coefficient and regression constant were calculated to assess the records simultaneously. Results: The frontal cephalometric measurements showed high correlation to the direct skull measurements (Pearson's coefficient 0.943<r<0.998) Conclusions: The linear measurements of the lateral cephalometric record are greater than the corresponding frontal cephalometric images. The overall findings of the present study showed that the frontal cephalometric measurements are closely related to the direct skull measures.